Reduction of Anxiety with Education to Menopausal Women in RW 03 Coral Village Duren, Jember - Nuri Alawiyah, Heti; Kiswati (D'Nursing and Health Journal (DNHJ), 2024)
Background: Menopause is a period sometimes makes women physical and psychological disturbances such anxiety. Based on preliminary studies, majority of menopausal 7 out of 10 respondents (70%) in Karang Duren experienced symptoms anxiety facing menopause. Analyzing the decrease in anxiety by providing education to menopausal in RW 03 Karang Duren. Method: Pre-Experimental research design, research design is a pretest-post test where the researcher gives treatment to research subjects but before that measured first then after the treatment study group is measured again. Population in this study were all menopausal in RW 03, Karang Duren. The number of samples 38 menopausal who were taken by simple random sampling. Collecting data using a questionnaire and tested using the Wilcoxon test. Result: In this study, before giving education, most of the respondents experienced moderate anxiety, namely 21 (55.00%). Then after providing education, most of the respondents experienced mild anxiety, namely as many as 25 (63.00%). The results of data analysis using Wilcoxon statistical test obtained asymptotic significance value 0.000 (<0.05). Concluded that H0 is rejected, which means that providing education can reduce anxiety in menopausal in RW 03 Karang Duren. Conclusion: Providing education can reduce anxiety menopausal in RW 03 Karang Duren.